The Commission Model of Teaching - David Allen; Agata Handley (Escola Superior de Educação de Paula Frassinetti, 2022)
Dorothy Heathcote (1926-2011) is best known today for the "Mantle of the Expert" system of teaching, a drama method in which young people are asked to think of themselves as an "expert" team of some kind, who receive a fictional commission from an imaginary client. This "commission" forms the basis for a programme of teaching across the curriculum. In the "Commission Model," which she created in the early 2000s, there is a real commission, from a real client in the community. The aim, for Heathcote, was to break down barriers between schools and the outside world; to ensure that learning takes place in a context; and to empower children as active "citizens of the world". This article examines a Commission project which Heathcote led, to design a hospital garden; with particular reference to science elements in the project. It draws on original materials from the Dorothy Heathcote Archive.